Rancang Bangun Alat Fast Charging Baterai Type Swap dengan Fitur Pendingin - Kusumawardhana, Dharma Indi; Wahyudi, Bagus (Al-DYAS, 2024)
This research aims to design and build a Fast Charging Swap Type Device for electric motorcycles with integrated cooling features. An Arduino MEGA is used as the temperature controller and indicator for the device, while an ESP32 is used as a data logger reader. Additionally, it is hoped that this device can stabilize the temperature and maintain the charging voltage. The research method uses experimentation, which involves testing the battery through this device with varying currents of 12 A, 14 A, and 16 A, comparing the use of the cooling feature at 15 °C and without cooling. The purpose of the testing is to demonstrate the performance of the fast charging swap type device. A data logger is used to monitor the stability of the DC voltage when using the cooling system and without it. The data is then processed into graphs. The collected data is subsequently analyzed using process testing methods and ANOVA testing.